EFFECT OF SUPPLEMENTATION OF LOCAL BREWERY BY-PRODUCTS ON FEED INTAKE, BODY WEIGHT CHANGE AND ECONOMIC EFFICIENCY OF WOYTO-GUJI GOATS FED HAY-BASED DIETS - Kaysimo, Geremu; Tadele, Yilkal (Chilean Journal of Agricultural & Animal Sciences, 2024)
Local brewery byproducts such as atella and tata, resulting from several fermented beverages, are used as animal feed in Ethiopia. However, there is no sufficient information on the nutritional value of those feed resources for animals. The objective of this study was to evaluate the effects of supplementing local brewery by-products on feed intake, body weight change, and economic profitability of Woyto–Guji goats fed on hay. Twenty-four yearling intact Woyto-Guji male goats were used. The experiment was conducted using a completely randomized block design. The goats were blocked into six groups of four animals based on initial body weight and randomly assigned to four different dietary treatments: hay alone (T1); hay combined with atella (T2); hay combined with tata (T3); and hay combined with an atella-tata mixture (1:1) (T4). The crude protein content of hay, atella, tata, and the atella-tata mixture used in this study were 7.35, 18.47, 17.51 and 17.86%, respectively. Dry matter reached values intakes of 564.56 (T1), 810.27 (T2), 850.37 (T3), and 945.85 (T4) g/day, and crude protein content recorded values intakes of 45.27 (T1), 104.18 (T2), 103.79 (T3), and 112.96 (T4) g/day were recorded. Total body weight gains were 2.76, 8.03, 6.15 and 9.72 Kg for the same treatments, respectively. Atella and tata, either supplemented alone or combined, increased body weight. The highest body weight gain was recorded in goats fed atella-tata mixture. All treatments had a positive net return.